2013
DOI: 10.1002/app.39178
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on β‐polypropylene/PP‐g‐MAH/surface treated talc composites

Abstract: Abstractβ‐Polypropylene composites containing talc treated by titanate coupling agent (T‐talc) and maleic anhydride grafted PP (PP‐g‐MAH) were prepared by melt compounding. The crystallization, morphology, and mechanical properties of the composites were investigated by means of differential scanning calorimetry (DSC), wide angle X‐ray diffraction (WAXD), polarized light microscopy (PLM), scanning electron microscopy (SEM), and mechanical tests. It is found that β nucleating agent (NT‐C) induces the formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The average values of n for pure, nucleated iPP and phPOSS modified samples were equal to 3.88; 3.73; and 5.37, correspondingly. As the first two values were close to 4 the process of thermal nucleation and three‐dimensional spherical growth could occur in such case . For all considered cooling rates of phPOSS modified samples, these values were significantly higher than for pure and nucleated iPP.…”
Section: Resultsmentioning
confidence: 73%
“…The average values of n for pure, nucleated iPP and phPOSS modified samples were equal to 3.88; 3.73; and 5.37, correspondingly. As the first two values were close to 4 the process of thermal nucleation and three‐dimensional spherical growth could occur in such case . For all considered cooling rates of phPOSS modified samples, these values were significantly higher than for pure and nucleated iPP.…”
Section: Resultsmentioning
confidence: 73%
“…The characteristic morphology of β-spherulites, originating after mixing iPP with Ca-pimelate, is also clearly illustrated in Fig. The Avrami plots for BNP and the model BNP/glass fiber composites in the investigated region of crystallization temperatures, similarly to other β-nucleated systems, [42][43][44] were almost linear (Fig. The K β parameter determined from the XRD-patterns by the Turner-Jones method 35 was 0.94, while the U β -value calculated from the melting endotherm was 0.84 ( Fig.…”
Section: Resultsmentioning
confidence: 77%
“…The β‐PP could be formed through CaCO 3 treated with pimelic acid (PA) and malonic acid (MA), wollastonite treated by PA and MA, mica treated by PA, eggshell modified by PA, zeolite modified by PA, montmorillonite modified by PA, as well as CaO and BaO treated by PA. Zhan et al found that multiwalled carbon nanotube (MWCNT) supporting N,N ′‐dicyclohexyl‐1,5‐diamino‐2,6‐naphthalenedicarboxamide could effectively induce the formation of β‐crystals in PP. Some researchers have introduced β‐nucleating agent into the PP matrix to create β‐PP, and β‐PP composites containing CaCO 3 , talc, mica, glass flake, organo‐montmorillonite, MWCNT, zeolite and inorganic fullerene‐like tungsten disulphide. Liu et al used halloysite nanotube (HNT) as a β‐nucleating agent, and the composite with 20 phr of HNT had the highest amount of β phases.…”
Section: Introductionmentioning
confidence: 99%